Respuesta :
Answer:
y-1=-2/3(x+9)
Step-by-step explanation:
y-1=-2/3(x-(-9))
y-1=-2/3(x+9)
Hello!
To write an equation for this line, you must follow these steps:
1. M= Slope (-2/3)
2. X1= -9
3. Y1= 1
4. First, take the equation y - y1 = m(x - x1)
5. Plug the values into the equation
6. Y - 1 = -2/3(x - (-9))
7. Change the sign
8. Y - 1 = -2/3(x +9)
9. Distribute the -2/3
10. Y - 1 = -2/3x - 6
11. Add 1 to both sides
12. Y = -2/3x - 5
This gives you a final answer of y = -2/3x -5 (note that this equation is in slope intercept form)
Hope this helps!
To write an equation for this line, you must follow these steps:
1. M= Slope (-2/3)
2. X1= -9
3. Y1= 1
4. First, take the equation y - y1 = m(x - x1)
5. Plug the values into the equation
6. Y - 1 = -2/3(x - (-9))
7. Change the sign
8. Y - 1 = -2/3(x +9)
9. Distribute the -2/3
10. Y - 1 = -2/3x - 6
11. Add 1 to both sides
12. Y = -2/3x - 5
This gives you a final answer of y = -2/3x -5 (note that this equation is in slope intercept form)
Hope this helps!